Contribution of magnetotail currents to Dst index during different intensity magnetic storms: a global MHD model study - Yue, Jiawen; Guo, Xiaocheng; Wang, Yuxian; Wang, Chi (Frontiers in Astronomy and Space Sciences, 2026)
The Disturbance Storm Time (Dst) index serves as a critical indicator for quantifying geomagnetic storm intensity; however, the precise contribution of magnetotail currents to its formation remains inadequately characterized. Based on a global magnetospheric magnetohydrodynamics (MHD) model, this study quantifies the contribution of magnetotail currents to the Dst index during geomagnetic storms of varying intensities. The Biot-Savart law was applied to integrate the magnetotail current density, computing the corresponding magnetic perturbation at Earth center in order to quantify the contribution of the magnetotail current to the Dst index. This study analyzed 20 geomagnetic storm events spanning varying intensities, with the majority occurring within the past 5 years. Simulation results indicate that the quantified contribution of magnetotail currents ranges from 23% to 26% during moderate storms, 20%–24% during intense storms, and falls below 20% during super storms. Thus, the relative contribution of magnetotail currents exhibits a robust decreasing trend with increasing storm intensity. This study is the first to employ a global MHD model to systematically quantify the contribution of magnetotail currents to the Dst index across varying geomagnetic storm intensities. These findings provide crucial quantitative evidence for understanding the role and dynamics of the magnetotail current system in geomagnetic storms, particularly highlighting its diminishing relative contribution during severe space weather events.